PENENTUAN TINGKAT KEMATANGAN TERMAL MINYAK MENTAH ( CRUDE OIL ) DARI LADANG MINYAK LIRIK Kab. INDRAGIRI HULU, RIAU - Cindya Afrina; Emrizal Mahidin Tamboesai; Halida Sophia (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Lirik oil field is one of the oil-producing layers that is located in Indragiri Hulu Riau province, situated at ± 140 km South of the city of Pekanbaru with the area of ± 12 km2. There is no researchon Lirik oil fields, at on the maturity level of petroleum using the methylphenantrene index parameters on oil wells, therefore this study aimed to determine the level of thermal maturity of Lirik oil. Determination of thermal maturity was done by taking two samples from two different wells of Lirik oil field, Riau. In this study the thermal maturity determination was done using two parameters, the parameters of isoprenoid and n-alkanes in saturated fractions and characterized using gas chromatography (GC-FID), this parameter was the initial parameter in the determination of thermal maturity. Determination of the level of thermal maturity of petroleum enhanced with Metilphenantrene index parameter on aromat fractions were characterized using gas chromatography -mass spectroscopy (GC-MS). Determination of thermal maturity level using the parameter index was determined by looking at the value Metilphenantren MPI-3 and MPR (Methylphenantrene ratio). The results of the determination of thermal maturity at saturated fraction using the ratio of n-alkanes and isoprenoid indicated that oil from Lirik oil wells, Riau was already ripen. This was confirmed by the parameters that have Metilphenantrene index values ranged MPI-3 0709; MPR 0755 and 0699 ranges; 0.756. The values of these parameters Metilphenantren index showed that crude oil from two wells Lirik, Riau has a low maturity level.